Polymorphism of mtDNA gene Cyt b of the Chukchi Sea polar cod, Boreogadus saida (Gadidae, Gadiformes) - Emelianova, Olga R.; Grigorov, Igor V.; Orlov, Alexei M. 1960-; Orlova, Svetlana Yu (Deep sea research. Part II: Topical studies in oceanography)
Polar cod (Boreogadus saida) is a species with an extensive pan-Arctic distribution. Although it is not an important target of commercial fisheries, due to its extremely high abundance and as a keystone species linking zooplankton with higher trophic levels of mammals and birds, polar cod are considered a critical component of the Arctic Ocean pelagic ecosystem. For the Chukchi and Beaufort Seas, either a complete absence of a popu-lation structure or very weak differences between this part of its range and others is shown. The purpose of this work is to identify the intraspecific organization of the polar cod based on mtDNA from most areas of the Chukchi Sea and the adjacent part of the Beaufort Sea. This is the first presentation of results from analysis of the Cyt b gene polymorphism of mitochondrial DNA in samples of polar cod from the western Chukchi Sea. Results indicated that there is no genetic differentiation of polar cod in the surveyed area. The exception are several samples from the Kotzebue Sound, central Chukchi Sea and western Beaufort Sea, which may be due to the transport of polar cod eggs, larvae or early juveniles by currents from the spawning grounds of Kotzebue Sound first to the central Chukchi Sea, and then to the western Beaufort Sea. The Kotzebue Sound population differs in nucleotide diversity index, as well as in pairwise values of the FST genetic differentiation index, which may be due to the isolation of this site from main currents in the area.